2015
DOI: 10.1016/j.juro.2015.01.126
|View full text |Cite
|
Sign up to set email alerts
|

Gleason 6 Prostate Cancer: Translating Biology into Population Health

Abstract: Purpose Gleason 6 (3+3) is the most commonly diagnosed prostate cancer among men with prostate specific antigen screening, the most histologically well differentiated and is associated with the most favorable prognosis. Despite its prevalence, considerable debate exists regarding the genetic features, clinical significance, natural history, metastatic potential and optimal management. Materials and Methods Members of the Young Urologic Oncologists in the Society of Urologic Oncology cooperated in a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 48 publications
1
50
1
Order By: Relevance
“…For many years, the definition of pathologically insignificant PCa was based on the pathological Epstein criteria, including a TV <0.5 cm 3 , Gleason score 6 and stage pT2 on prostatectomy [7]. More recent epidemiological data have shown that a TV of <0.5 cm 3 is a considerable underestimation of the threshold for pathologically insignificant PCa [8].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, the definition of pathologically insignificant PCa was based on the pathological Epstein criteria, including a TV <0.5 cm 3 , Gleason score 6 and stage pT2 on prostatectomy [7]. More recent epidemiological data have shown that a TV of <0.5 cm 3 is a considerable underestimation of the threshold for pathologically insignificant PCa [8].…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, rebiopsy is associated with complications and mental distress, 5 and is thus a serious problem for both patients and physicians alike. 1 More reliable and less invasive methods are required for favorable outcomes after AS.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Many of these men do not benefit from immediate treatment and thus could be managed expectantly, a strategy currently known as AS. 1 Identification of such patients is usually based on the biopsy findings and values of PSA and its derivatives, such as PSAD. 2 The rate of PSA change over time, known as PSA dynamics or kinetics, was conceptually introduced by Carter in 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Active surveillance (AS) is a treatment option for men with low-risk prostate cancer, which addresses the overtreatment of indolent cancers [47]. Many different AS protocols exist, which are based on multiple clinical parameters as well as the pathology results from standard sextant biopsy sessions.…”
Section: Active Surveillancementioning
confidence: 99%